Instructional Crisis Communication for an Industry: Model and Anti-Model Biosecurity Standards for the Prevention and Control of Highly Pathogenic Avian Influenza - Ronisha J. Sheppard; Timothy L. Sellnow; Deanna D. Sellnow; Adam J. Parrish; Jeffrey D. Brand (Journal of Applied Communications, 2020)
Highly pathogenic avian influenza (HPAI) is a global disease that is increasing in both frequency and intensity in North America. Recent outbreaks of HPAI in Iowa, Minnesota, and Indiana resulted in the cumulative loss of millions of birds and over a billion dollars for poultry farmers. This study examined the instructional communication used by state and national responders to promote effective biosecurity intended to limit the spread and impact of HPAI in the three recent outbreaks in the United States. Specifically, the researchers asked, what biosecurity strategies serve as an instructional model for an effective crisis response, and, conversely, what biosecurity strategies serve as an instructional anti-model for an effective crisis response during an HPAI outbreak? Perelman and Olbrechts-Tyteca’s (1969) conceptual framework for model and anti-model arguments guided the analysis. Model strategies include maintaining lines of separation protecting healthy birds from exposure, providing instruction that presents biosecurity practices as feasible for workers, having supervisors model the appropriate biosecurity practices, adapting biosecurity plans to fit the needs and resources of individual farms, and realizing the importance of mental health for farmers facing the loss of their animals. Anti-model practices were seen as breaches of the model recommendations. Practical applications include providing instructions on maintaining a line of separation and avoiding common errors, consistently engaging in a biosecurity workable plan prior to outbreaks, providing adequate and timely biosecurity messages as part of a comprehensive and coordinated communication plan uniting farmers, state, and national agencies, and monitoring the mental wellbeing of impacted farmers.
Keywords: Risk Communication; Crisis Communication; Instructional Communication